Association Between the Degree of Inclusion of Components Identified on Fluorescein or Indocyanine Green Angiography in Target Spots and Relapse of Exudate in Eyes with Polypoidal Choroidal Vasculopathy and Typical Age-Related Macular Degeneration After Photodynamic Therapy - Yoshida, Izumi; Taniguchi, Hikari; Sakamoto, Masashi; Maeno, Takatoshi (Clinical ophthalmology (Auckland, N.Z.), 2021)
To investigate the association between the inclusion of components identified on images in target spots of photodynamic therapy (PDT) and exudate relapse in eyes with age-related macular degeneration (AMD). Forty-one eyes (39 patients) with polypoidal choroidal vasculopathy (PCV) and 32 eyes (31 patients) with typical AMD (tAMD) who underwent PDT were retrospectively investigated. Each component identified on fluorescein (FA) or indocyanine angiography (IA), optical coherence tomography (OCT), or color photography was graded as not depicted, covered with a margin ≥500 µm or <500 µm, and protruding. Associations between these grades and the dry rate (proportion of subjects with continuous absence of exudate over following 12-month period) and the relapse index (2 × number of injections administered + accumulation of exudate for 12 months post-PDT) were investigated. In PCV, the association between worse coverage and decreasing dry rates for feeder vessels and polyps approached statistical significance. With coverage margins ≥500 µm, dry rate tended to be greater than with coverage margins <500 µm for feeder vessels, classic lesions, and occult lesions on FA. In the tAMD group, coverage with margins ≥500 µm tended to yield a higher dry rate than coverage with margins <500 µm for CNV on IA. Coverage with margins ≥500 µm for occult and classic lesions on FA yielded no dry subjects, and all subjects with classic lesions or staining had recurrence (P = 0.009 and 0.050). Worse coverage and worse dry rate in PCV and worse relapse index in tAMD were related to pigment epithelial detachment on OCT (P = 0.040 and 0.006). Polyps in PCV and pigment epithelial detachment (PED) in tAMD were verified as appropriate targets, corresponding to the existing guidelines, and feeder vessels, classic lesion, occult lesion, and PED in PCV and CNV on IA in tAMD were suggested as further targets. OCT was superior to FA for evaluating PED.